Anti-Inflammatory Effects of Cold Thermal Therapy on Allergic Skin Inflammation Induced by Trimellitic Anhydride in BALB/c Mice. (28th January 2019) - Piao, Chun Hua; Kim, Minjoo; Bui, Thi Tho; Hyeon, Eunjin; Fan, Yanjing; Song, Chang Ho; Jeong, Hwan-Jeong; Chai, Ok Hee
Abstract : Cold and hot thermal therapies are widely used as a traditional therapy in many cultures and are often prescribed in the treatment of various musculoskeletal and neurological conditions which present themselves to primary care physicians. However, there are no reports that investigated either the effects of cold and hot thermal therapies on the skin inflammation of trimellitic anhydride- (TMA-) induced dermatitis-like contact hypersensitivity (CHS) mouse model, or the mechanism of thermal therapy on allergic skin inflammation. Therefore, in this study, to reveal the anti-inflammatory effect of thermal therapy and its mechanism on TMA-induced CHS, we analyzed ear-swelling response (ear edema), vascular permeability, serum IgE levels, histological examination, and histamine and Th2 cytokine levels. Cold thermal therapy reduced the ear-swelling response, the vascular permeability, the serum IgE levels, and the infiltration of eosinophils and mast cells as well as the mast cell degranulation. To determine the mechanism by which cold thermal therapy inhibits allergic skin inflammation, detailed studies were carried out revealing that cold thermal therapy suppressed IL-4 and IL-5 secretion and mast cell activation. These results indicated that cold thermal therapy cures skin inflammation of TMA-induced CHS by decreasing Th2 cytokine release, especially IL-4 and IL-5, and mast cell activation. These data suggest that new insight into the mechanism of robust therapeutic effects of cold thermal therapy against allergic dermatitis, and cold thermal therapy may prove to be a useful therapeutic modality on allergic inflammatory diseases as traditional use as well as Th2- or mast cell-mediated allergic responses.